2019
DOI: 10.5935/1518-0557.20190037
|View full text |Cite
|
Sign up to set email alerts
|

Assisted reproductive techniques in Latin America: The Latin American registry, 2016

Abstract: Research question: What was the utilization, effectiveness and perinatal outcome of assisted reproductive technologies (ART) performed in Latin America during 2016 Design: Retrospective collection of multinational data on ART performed in 178 institutions from 15 Latin American countries. Results: We are reporting 85,474 initiated cycles, 15,070 deliveries and 18,182 babies born in this period. Of all fresh autologous IVF/ICSI cycles, 40.9% w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 6 publications
0
15
0
2
Order By: Relevance
“…17,18 Nevertheless, the scenario will probably improve in Latin America in the near future, since Argentina, Chile and Uruguay have changed their laws in 2013, providing universal access to ART, which will probably result in improved ART quality parameters in upcoming RLA reports. 18,19 Some countries in the European registry allow public access to the individual results of the clinics, a practice that also occurs in the US report. 20,21 The RLA does not report these data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…17,18 Nevertheless, the scenario will probably improve in Latin America in the near future, since Argentina, Chile and Uruguay have changed their laws in 2013, providing universal access to ART, which will probably result in improved ART quality parameters in upcoming RLA reports. 18,19 Some countries in the European registry allow public access to the individual results of the clinics, a practice that also occurs in the US report. 20,21 The RLA does not report these data.…”
Section: Discussionmentioning
confidence: 99%
“…Our strategy for the present ecological study was to search scientific publications in Latin America and in Europe that reported data collection for the same time periods: data from ART performed in 2013 in Latin America and Europe (i.e., treatment cycles initiated between January 1 and December 31, 2013), and published by the ESHRE in 2017 and by the RLA in 2016. 8,9 As only members of the ESHRE and of the RLA can access and use the full registry databases for research purposes, we focused our comparisons in the published, summarized data. No Institutional Review Board approval was therefore required, since neither patients nor center level data were used.…”
Section: Data Extraction and Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Delivery rates per cycle in REDLARA are 25.05% for ICSI and 27.41% for IVF, respectively 7 , which are very similar to results in the United States and the best centers in Europe. However, PGT in all of Latin America is importantly limited compared to Europe and the US, with 2119 PGT cycles and only 95 deliveries, with a delivery rate per initiated fresh cycle of 4.7% and 36.40% delivery rate per embryo transfer in 2014 7 . Unfortunately, the REDLARA data on PGT 7 do not differentiate between PGT-A and PGT-M cycles to better estimate how often PGT-M is used in Latin-American countries to prevent Mendelian disorders.…”
Section: Discussionmentioning
confidence: 99%
“…The method of collecting data in 2017 resembles previous years (Zegers-Hochschild et al, 2019), making results comparable. Definitions used refer to the latest publication of the International glossary on Infertility and Fertility Care (Zegers-Hochschild et al, 2017).…”
Section: Methodsmentioning
confidence: 99%